2019
DOI: 10.1002/fuce.201800205
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Impedance Spectroscopy of Electrospun La0.6Sr0.4Co0.2Fe0.8O3–δ Nanorod Cathodes for Intermediate Temperature – Solid Oxide Fuel Cells

Abstract: Electrospun La0.6Sr0.4Co0.2Fe0.8O3–δ (LSCF) nanorod cathodes are investigated. Morphological characterization shows that the nanorods are arranged into a 3‐D stochastic structure, with multiple contact points with each other. Experimental characterization of symmetrical button cells through electrochemical impedance spectroscopy demonstrates an electrode polarization resistance Rp = 3.9 Ω cm2 at 940 K and Rp = 10.9 Ω cm2 at 890 K. The impedance results, measured from 890 K up to 1,200 K, show that the depresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…The evolution of the impedance diagrams at OCP are given in Fig 7a and 7b for oxygen partial pressures ranging from 0.1 to 1 atm. It can be noticed that the electrode polarization resistance significantly decreases when increasing the oxygen content, as already experimentally observed in [49,74,75]. The reaction order m was estimated fitting the experimental data with the following relation:…”
Section: Experimental Results and Model Validation 41 Electrode 3d Reconstructions And Electrochemical Characterizationsmentioning
confidence: 73%
See 1 more Smart Citation
“…The evolution of the impedance diagrams at OCP are given in Fig 7a and 7b for oxygen partial pressures ranging from 0.1 to 1 atm. It can be noticed that the electrode polarization resistance significantly decreases when increasing the oxygen content, as already experimentally observed in [49,74,75]. The reaction order m was estimated fitting the experimental data with the following relation:…”
Section: Experimental Results and Model Validation 41 Electrode 3d Reconstructions And Electrochemical Characterizationsmentioning
confidence: 73%
“…These reaction orders are in rather good agreement with literature data. For instance, an exponent of 0.12 was deduced for a LSCF nanorod electrode operated at 717 °C in a range of oxygen partial pressure ∈ [0.10 -0.20] atm [75].…”
Section: Experimental Results and Model Validation 41 Electrode 3d Reconstructions And Electrochemical Characterizationsmentioning
confidence: 99%
“…[2,13,35,39] Despite the presence of both electronic and ionic conductivity inside the core-shell nanofiber electrode, in the EIS results in Figure 5 there is no presence of Gerischer behavior which is well detected in the case of MIECs, i. e. La 1-x Sr x Co y Fe 1-y O 3-δ . [21][22][23][24]40] This can be inferred from the Nyquist plots in Figure 5, where none of the arcs shows the high-frequency line with a 45°slope typical of Gerischer behavior. In parallel, all the attempts to fit the EIS experimental data with ECs embedding a Gerischer element failed.…”
Section: Electrochemical Characterizationmentioning
confidence: 79%
“…Indeed, LSCF and BSCF can conduct both electrons and oxygen ions extending the triple-phase-boundary (TPB) in the entire electrode volume. [8,9,[20][21][22][23][24][25] However, due to the recent geopolitical problems related to Co extraction and commercialization, Cofree materials are intensively studied. Cu is currently under investigation as a substitute.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from catalysis, it is demonstrated that the electrospun copper oxide fiber can be reduced to copper fiber for transparent electrode application [11]. Going beyond simple binary oxides, La 0.6 Sr 0.4 Co 0.2 Fe 0.8 O 3-δ perovskite oxide fiber was utilized to fabricate a solid oxide fuel cell air electrode [12].…”
Section: Introductionmentioning
confidence: 99%